Handbook of HIV medicine - Wilson, Douglas (Physician) (Cape Town ; New York : Oxford University Press, 2008)
[Publisher-supplied data] The Handbook of HIV Medicine, 2nd edition, is an invaluable practical guide for practitioners at varying levels of expertise who deal with HIV/AIDS in a variety of contexts, from counseling to prescribing antiretroviral medicine. It also serves as a teaching aid for medical students. New chapters in the 2nd edition include: Prevention of HIV, Tuberculosis, Adherence, ARV Resistance and Resistance Testing, Drug Interactions, Immune Reconsitution Syndrome, Management of Adverse Drug Reactions, and Starting an ARV Clinic.
General introduction to HIV medicine -- Approach to HIV infection in children -- Approach to HIV infection in adults -- Systemic approach to HIV infection -- Drug management -- Patient-centered care.
Includes bibliographical references and index.
Keywords: HIV infections -- Handbooks, manuals, etc; HIV infections -- Treatment -- Handbooks, manuals, etc; HIV infections; HIV Infections; Anti-Retroviral Agents -- therapeutic use